2016
DOI: 10.1186/s40001-016-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Waiting time for radiation therapy after breast-conserving surgery in early breast cancer: a retrospective analysis of local relapse and distant metastases in 615 patients

Abstract: BackgroundPostoperative radiotherapy after breast-conserving surgery (BCS) is the standard in the management of breast cancer. The optimal timing for starting postoperative radiation therapy has not yet been well defined. In this study, we aimed to evaluate if the time interval between BCS and postoperative radiotherapy is related to the incidence of local and distant relapse in women with early node-negative breast cancer not receiving chemotherapy.MethodsWe retrospectively analyzed clinical data concerning 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Previous studies have attempted to define the role of TI in predicting the tumor prognosis; however, their findings were inconsistent. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] One previous study that included 18 050 breast cancer patients treated with surgery and adjuvant radiotherapy, reported that a long TI was associated with the increased likelihood of local recurrence (hazard ratio=1.19, 95% confidence interval: 1.01 to 1.39, P=0.033). 6 A systematic review of 34 relevant studies with a total of 79,616 breast cancer patients reported that the relative risk of local recurrence per month of delay was 1.08 (95% confidence interval 1.02-1.14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have attempted to define the role of TI in predicting the tumor prognosis; however, their findings were inconsistent. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] One previous study that included 18 050 breast cancer patients treated with surgery and adjuvant radiotherapy, reported that a long TI was associated with the increased likelihood of local recurrence (hazard ratio=1.19, 95% confidence interval: 1.01 to 1.39, P=0.033). 6 A systematic review of 34 relevant studies with a total of 79,616 breast cancer patients reported that the relative risk of local recurrence per month of delay was 1.08 (95% confidence interval 1.02-1.14).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Caponio et al, in which 615 breast cancer patients were divided into three groups according to the timing of radiotherapy (≤60, 61–120, and >120 days) and followed up for 15 years, reported no relationship between the TI and the risk of local recurrence. 11 In another study, Barbieri et al included a total of 387 patients with T1-2 breast cancer were treated with breast-conserving surgery and radiotherapy, showing no impact of a delay in radiotherapy on the risk of local relapse. 12 However, a major limitation of this study was in the selection criteria, which did not consider the differences in TI between patients who did and did not undergo chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…is supports the evidence that receiving radiation or not could be considered as an independent variable. e time of radiation therapy after surgery is another challenging issue, which is not approved in many independent studies [40][41][42][43]. In a trial with 16 years follow-up, RT confirmed no increased risk of local recurrence when administered 2, 4, and 7 months after surgery and initial systemic therapy [44].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that there was no decreased in survival or increased local or distant recurrence, 4.5 while other studies found that there was a decreased in survival and increased local recurrence in patients who received radiotherapy more than 6 weeks. 5 Because of differences in the results of the study, we were interested to make this critical appraisal.…”
Section: Introductionmentioning
confidence: 99%